Strategies for product-line verification: case studies and experiments - Apel, Sven; Rhein, Alexander von; Wendler, Philipp; Größlinger, Armin; Beyer, Dirk (Proceedings of the 2013 International Conference on Software Engineering, 2013)
Product-line technology is increasingly used in mission-critical and safety-critical applications. Hence, researchers are developing verification approaches that follow different strategies to cope with the specific properties of product lines. While the research community is discussing the mutual strengths and weaknesses of the different strategies—mostly at a conceptual level—there is a lack of evidence in terms of case studies, tool implementations, and experiments. We have collected and prepared six product lines as subject systems for experimentation. Furthermore, we have developed a model-checking tool chain for C-based and Java-based product lines, called SPLVERIFIER, which we use to compare sample-based and family-based strategies with regard to verification performance and the ability to find defects. Based on the experimental results and an analytical model, we revisit the discussion of the strengths and weaknesses of product-line–verification strategies.